Nutrient release from rice and rubber biochar tablets with and without embedded fertilizers - Lee, Yit Leng (2021)
An alternative to agricultural residues management is to convert them to biochar because this organic amendment can act as a superior soil conditioner that improves soil productivity. Nevertheless, the low density of biochar poses a challenge in the handling biochar. Tableting of biochar can mitigate the aforementioned problems associated with biochar. The objectives of this study were to determine the physico-chemical properties, nutrient release and soil ammonia volatilization of biochar tablets with and without embedded fertilizers. The different rates of biochar tablets with and without embedded fertilizers impact on selected soil chemical characteristics and nutrient use efficiency (NUE) of sweet corn (test crop) were also determined. Next planting cycle was conducted to determine the effects of combination biochar and fertilizers with and without tableting on selected soil chemical characteristics and NUE of sweet corn (test crop).